Correlation and Path Coefficient Analysis of Yield Components in Advanced Lines of Grasspea (Lathyrus sativus L.) - Kour, Jaspreet; Agarwal, Neha (International Journal of Bio-resource and Stress Management, 2023)
The present study was undertaken with eighteen advanced lines with their five parents were grown during rabi 2011 in Randomized Complete Block Design (RBD) with three replications in plot size of 4×0.45 m2 at row spacing of 30 cm apart. The observations for 15 biometric characters viz., length of the first bearing node (cm), days to 50% flowering, days to maturity, number of pods plant-1, number of seeds pod-1, number of seeds plant-1, seed yield plant-1 (g), 100 seed weight (g), plant biomass plant-1 (g), harvest index (%), swelling index, seed protein content (%) and ODAP content (%) at flowering, pod filling and maturity stages were recorded on five plant basis in each plot in each replication. Positive genotypic correlation was shown by harvest index, number of seeds plant-1, plant biomass plant-1 and number of pods plant-1. Yield was positive and significantly correlated with seed ODAP content, biomass plant-1, harvest index, days to maturity, number of seeds pod-1, length of first bearing node and number of pods plant-1. Seed ODAP content, biomass plant-1, harvest index, days to maturity, number of seeds pod-1, length of first bearing node and number of pods plant-1 contributed maximum positive and direct effect on yield indicating these traits should be given emphasis while selecting high yielding cultivars. Our results indicated from the present study that traits showing strong and positive correlation with seed yield may be given priority while characters showing negative correlation should avoid during selection of superior genotypes for improving seed yield in grasspea.